THE EFFECT OF RQA (READING, QUESTIONING, ANSEWRING) LEARNING STRATEGY ASSISTED BY GOOGLE CLASSROOM ON STUDENTS’ COGNITIVE LEARNING OUTCOMES ON STATIC FLUIDS TOPIC - Nainggolan, Elfi Dwi Ansa; Sirait, Makmur (UNIVERSITAS NEGERI MEDAN, 2022)
This study aims to: 1) determine students’ cognitive learning outcomes using RQA learning strategy assisted by Google Classroom on Static Fluids topic, 2) determine students’ cognitive learning outcomes using expository learning strategy assisted by Google Classroom, and 3) to prove the effect of RQA learning strategy assisted by Google Classroom on students’ cognitive learning outcomes on static fluids topic for class XI SMA N 1 Percut Sei Tuan. The type of research is a quasi-experimental research design with Pretest-Postest Group Design. The population of this research is all students of class XI SMA N 1 Percut Sei Tuan which consists of 6 classes. The sample of this research was taken by using simple random sampling technique, namely class XI MIPA 5 as the experimental class and XI MIPA 6 as the control class, each consisting of 23 students and 20 students. The instrument used is achievemnet test, namely a multiple choice test consisting of 10 items. The results of data analysis showed the average pretest value of the experimental class was 54.35 and the control class was 47.50. After being given treatment, the average posttest value for the experimental class was 75.05 and the control class was 53.00. By using the one sample t-test obtained the value of Sig. (2-tailed) < 0.05 (0.00 < 0.05) so Ha is accepted and H0 is rejected. So it can be concluded that there is a significant effect due to the use of RQA learning strategies assisted by Google Classroom on students' cognitive learning outcomes of XI MIPA on static fluids topic.